MODEL PENINGKATAN KINERJA KARYAWAN PADA POLRES SALATIGA MELALUI FAKTOR KEPUASAN KERJA DAN KOMITMEN ORGANISASI - Taufik Akbar Karim (Jurnal Riset Bisnis Indonesia, 2013)
This research aims to describe and analyze (1) the influence of psychological satisfaction, socialsatisfaction and other psychical satisfaction toward performance of human resources Salatiga PoliceResort, (2) the influence of psychological satisfaction, social satisfaction and other psychical satisfactiontoward commitment organization, and (3) the influence of commitment organization toward theperformance of human resources in Salatiga police resort. 78 paticipants who are the police officersof salatiga Police Resort were involved in this study, based on Slovin formula. Path analysis wasused as the analysis method. The results of the study show that: (1) psychological satisfaction has apositive significant influence on human resources performance at Salatiga police resort, (2) psyichalsatisfaction has a positive significant influence on human resources performance at Salatiga policeresort, (3) social satisfaction has a positive significant influence on human resources performanceat Salatiga police resort, (4) psychological satisfaction has a positive significant influence oncommitment organization, (5) phsycal satisfaction has a positive significant influence on commitmentorganization, (6) social satisfction has a positive significant influence on commitment organization,(7) commitment organization has a positive significant influence on human resources performanceat Salatiga police resort, (8) there is no positive significant influence of psychological satisfactionon human resources performance at Salatiga Police Resort through commitment organization asintervening variable, (9) there is no positive significant influence of phsyical satisfaction on humanresources performance at Salatiga Police Resort through commitment organization as interveningvariable, (10) there is no positive significant influence of social satisfaction on human resourcesperformance at Salatiga Police Resort through commitment organization as intervening variable.Keywords: Psychological Satisfaction, Physical Satisfaction, Social Satisfaction, CommitmentOrganization, the Performance of Human Resources